A PHARMACO-ECONOMIC ANALYSIS OF TREATMENT EFFICACY INTEGRATING HCV DIAGNOSIS AND TREATMENT (Uz Conferences, 2025)
This article delves into the realm of pharmaco-economics by conducting a comprehensive analysis of the efficacy of treatments for Hepatitis C Virus (HCV) while integrating both diagnosis and treatment processes. The authors explore the economic implications of various treatment strategies, considering factors such as cost-effectiveness, healthcare resource utilization, and patient outcomes. By integrating HCV diagnosis into the analysis, the article aims to provide a holistic perspective on the economic impact of different treatment approaches. This study contributes valuable insights for healthcare policymakers, clinicians, and researchers seeking to optimize HCV management strategies within the constraints of healthcare budgets and resource allocation. The findings presented in this article are expected to inform decision-making processes regarding HCV treatment policies, ultimately striving for improved patient outcomes and efficient allocation of healthcare resources